Dewan Hisbah Sebagai Lembaga Otoritas Keagamaan PERSIS - Nihayatut Tasliyah (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
PERSIS is an influential religious organization in Indonesia, as well as Nahdlatul Ulama (NU) and Muhammadiyah. The existence of such organizations is supported by the organizational units that are authorized to formulate religious instruction. The organizational unit is called Hisbah Council. This article described the Istinbath method and some of the decisions made by the Hisbah Board